2004
DOI: 10.1191/1362168804lr133oa
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and user acceptance of peer rating in EFL writing classrooms

Abstract: Lack of research on the characteristics of peer assessment in E FL writing may inh ibit teachers from appreciating the utility of this inno vative assessment. This study addr essed the followin g research questions: (1) H ow similar are peer, self-and teacher ratings of E FL writing?; (2) D o students favour peer ratings?; and (3) D oes peer feedb ack influence students' attitudes about peer rating? Forty-seven college students stud ying E nglish writing in a Japanese college were assigned to write two essays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 48 publications
7
70
2
1
Order By: Relevance
“…This is in line with the studies of AlFallay (2004), Patri (2002), and Saito and Fujita (2004) who reported the high coefficients between teacher-assessment and peer-assessment (r= .92, .85, and .72, respectively). In general, all correlations obtained in this study were significant and relatively high (ranged .55 to .87).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is in line with the studies of AlFallay (2004), Patri (2002), and Saito and Fujita (2004) who reported the high coefficients between teacher-assessment and peer-assessment (r= .92, .85, and .72, respectively). In general, all correlations obtained in this study were significant and relatively high (ranged .55 to .87).…”
Section: Discussionsupporting
confidence: 78%
“…Although the unreliability of self-and peer-assessment limits some teachers to use them only for developmental purposes (Saito & Fujita, 2004), one should keep in mind that even experienced teachers are not always reliable markers and so it seems unreasonable to expect inexperienced students always to demonstrate reliability (Falchikov & Boud, 1989). This means that the limitations should not downgrade the pedagogical values of self-assessment and peer-assessment in language education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies have shown that peer assessment is interrelated with instructor assessment (Jafarpur, 1991;Patri, 2002;Saito & Fujita, 2004). Saito (2008) proved that training could improve the quality of peer assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[2,3]). Both self and peer assessment can be used to assess writing [4,5,6,7,8] as well as presentations [9].…”
Section: Introductionmentioning
confidence: 99%